2015
DOI: 10.1016/j.fertnstert.2015.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Single human sperm cryopreservation method using hollow-core agarose capsules

Abstract: A cryopreservation method for a single sperm using an agarose capsule has been developed. The method is expected to be useful in ICSI treatment in patients with few spermatozoa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Agarose capsules were produced according to the method described in a previous study 13 . Briefly, alginate beads were prepared using 0.5% calcium carbonate and 4% alginate acid solutions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agarose capsules were produced according to the method described in a previous study 13 . Briefly, alginate beads were prepared using 0.5% calcium carbonate and 4% alginate acid solutions.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Araki et al . produced an agarose capsule that can be used to store sperm individually 13 . The shape of the agarose capsule is extremely similar to that of the ZP, and it is possible to create a capsule with a ZP-like size.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, sperm cryopreservation is a critical part of assisted reproductive technology (ART) (Araki et al, 2015; Tomita et al, 2016; Zou et al, 2013), while most of the applications of microfluidics in sperm processing were focused on sorting or isolation of sperm from semen sample; few studies were found on CPA addition and removal (Cho et al, 2003; Huang et al, 2014; Li et al, 2016; Samuel et al, 2016; Sano et al, 2010; Schuster et al, 2003). Fortunately, both the designs for the staggered herringbone microfluidic mixer (Park et al, 2012) and the passive, planar micromixer based on logarithmic spirals (Scherr et al, 2015; Scherr et al, 2012) (Figure 7E), which are initially developed for sperm activation, can be potentially adopted for CPA processing, since where controllable extracellular mixing is supplied.…”
Section: Controllable Addition and Removal Of Cpasmentioning
confidence: 99%
“…Furthermore, the high surface-area-to-volume ratio of cell suspension on a chip intrinsically enables rapid cooling and warming needed for vitrification. More importantly, this technique provides an urgently needed method for preserving very limited volumes of biological samples, as often occurs with assisted reproductive technologies and stem cell research (Araki et al, 2015; Cohen and Garrisi, 1997; Cohen et al, 1997; Montag et al, 1998; Rao et al, 2015; Wang et al, 2016). Microfluidics can further be used to produce biological agents and cells in micro-scale volumes, enabling low-CPA droplet or encapsulation vitrification (Choi et al, 2015a; He et al, 2008; Huang et al, 2015; Risco et al, 2007; Tasoglu et al, 2013).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation